DEVELOPMENT OF MATHEMATICS MODULE BASED ON LEARNING MODEL OF GUIDED INQUIRY IN SUB-MATERIAL ALGEBRA FOR JUNIOR HIGH SCHOOL CLASS VIII - Dwi Lestari; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The use of materials that are insufficient to cause the learning process centered on the teacher. It causes low student independence and liveliness in building his own, becomes a factor it needs alternative materials that can facilitate the student's independent study. Math algebra material on module into alternative materials that can be used by students. This research aims to develop a mathematical module and test the feasibility of the mathematics modules. The research design used, namely with the stages of Research and Development potential and problems, data collection, product design, design validation, revision of the design, product testing, product testing, revisions, and revision of the product. The subject of research is the study of the expert product, i.e., lecture of mathematics, mathematics teacher, and students. Types of data used, i.e., qualitative and quantitative data. Engineering data collection using a non-test with instruments in the form of sheets of interview and question form. With test instruments through the validation and analysis of data using lecturer analysis question form and analysis of the feasibility of a mathematical module. Based on the results of the study, the feasibility of mathematical module by material obtained an average score of 151 with the criteria of very good, the eligibility module by media expert gained an average of 167.33 criteria very good, and the now the response of students with an average of 130.7 and 127 with the criteria of very good. So, the mathematical content module algebra worth for use in learning.